Solid-state NMR studies of chromatin structure and dynamics - Prasanna, Chinmayi (Nanyang Technological University, 2021)
Understanding the dynamic organization of chromatin is indispensable as it provides crucial information to delineate cellular processes that it mediates–DNA replication, transcription, and repair. Nucleosome core particle (NCP) composed of core histones, organizing ~147 bp of DNA constitutes the fundamental unit of eukaryotic chromatin. While the structure of nucleosome is investigated predominantly using X-ray crystallography, quantitative information about nucleosome dynamics remains elusive. Our objective is to address this gap using solid-state nuclear magnetic resonance (SSNMR) spectroscopy, which is a state-of-the-art technology to probe protein dynamics at atomic resolution. We have conducted SSNMR experiments for human histones in the NCP at physiological chromatin concentrations to probe the site-specific motions and amplitudes. We also investigated the influence of histone dynamics in the context of nucleosomes in the chromatin fiber and the human telomeric repeat DNA sequence. Our study is the first to have probed quantitative motions of histones in the chromatin.